A heat-activated adhesive suitable for bonding aluminum honeycomb core laminated nodes and a preparation method thereof

By using a combination of heat-activated adhesives, including acrylonitrile-butadiene copolymer and bisphenol A epoxy resin, the problem of existing adhesives being easily softened at high temperatures is solved, firm bonding and precise honeycomb design of aluminum honeycomb structure nodes are achieved, and good heat resistance and environmental protection characteristics are provided.

CN118995084BActive Publication Date: 2025-03-28SHANGHAI SHENLIFU MEDICAL TECHNOLOGY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411473551.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-03-28
Estimated Expiration
2044-10-22

AI Technical Summary

Technical Problem

Existing adhesives tend to become soft at high temperatures, making it difficult to maintain high bonding strength, and the formaldehyde-induced properties of phenolic resins make them unable to be used in environmentally friendly products and cannot be suitable for node bonding of aluminum honeycomb structures.

Method used

A thermally activated adhesive is provided, and its raw material composition includes acrylonitrile-butadiene copolymer, bisphenol A epoxy resin, rubber vulcanizing agent, epoxy curing agent and coupling agent. Through heating activation, the aluminum foil stack is firmly bonded to form an accurate honeycomb design structure.

Benefits of technology

The adhesive is non-adhesive at room temperature and is suitable for node bonding of aluminum honeycomb core stacks. It forms a firm bond through heating activation. After the aluminum foil stack is unfolded, it forms an accurate honeycomb design structure and the nodes are constantly cracked. It does not use phenolic resin, and has good heat resistance and environmental protection characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118995084B_ABST
    Figure CN118995084B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of adhesives, and particularly relates to a heat-activated adhesive suitable for bonding nodes of aluminum honeycomb core laminates and a preparation method thereof. The raw material composition of the heat-activated adhesive suitable for bonding nodes of aluminum honeycomb core laminates includes: by mass percentage, 30-55% acrylonitrile-butadiene copolymer, 30-45% bisphenol A epoxy resin, 0.5-5% rubber vulcanizer, 5-18% epoxy curing agent, and 0.5-5% coupling agent; the solvent is not included in the raw material composition of the heat-activated adhesive suitable for bonding nodes of aluminum honeycomb core laminates. The heat-activated adhesive of the present invention is suitable for bonding between aluminum honeycomb core laminates. The adhesive layer after applying it on the surface of aluminum foil and drying is non-sticky at room temperature. When used, the multi-layer aluminum foil laminate is compacted by pressure, and the aluminum foil laminates are firmly bonded by heating activation. After the aluminum foil laminate is unfolded, a precise honeycomb design structure is formed and the nodes are not broken.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adhesives, and particularly relates to a heat-activated adhesive suitable for bonding laminated nodes of aluminum honeycomb cores and a preparation method thereof. Background Art

[0002] Compared with traditional materials, honeycomb structure materials are characterized by light weight, less material and low cost. They also have good sound insulation, electrical conductivity, heat resistance, corrosion resistance, energy absorption, shock absorption and heat insulation effects, as well as high strength, high temperature resistance and corrosion resistance.

[0003] Aluminum honeycomb panels are one of the common honeycomb structure products. The application fields of aluminum honeycomb panels are extremely broad. For example, aluminum honeycomb panels can be widely used in aerospace fields such as aircraft, helicopters, and satellites due to their light weight, high strength, flame retardancy, and corrosion resistance. For example, aluminum honeycomb structures can be widely used in rail transportation, especially in doors and ceilings of trains and subways, due to their sound absorption, heat insulation, and fire retardancy. In addition, aluminum honeycomb panels are also widely used in the construction field, such as in the production of sandwich panels, roof panels, ceilings, partitions, and furniture.

[0004] The core of aluminum honeycomb products lies in the aluminum honeycomb core. The production of aluminum honeycomb core requires the use of a coatable high-strength adhesive. The prior art generally uses a phenolic resin-nitrile rubber system adhesive or a phenolic epoxy resin-nitrile rubber system adhesive for node bonding of aluminum honeycomb core laminates. However, the phenolic resin-nitrile rubber adhesive system tends to soften at high temperatures, making it difficult to maintain high bonding strength, and easily causing the honeycomb core structure to be destroyed. In addition, the formaldehyde-releasing properties of phenolic resins make it impossible for phenolic resin-nitrile rubber adhesive systems or phenolic epoxy resin-nitrile rubber adhesive systems to be used in environmentally friendly products.

[0005] Chinese patent CN104479620B discloses a high temperature resistant honeycomb node adhesive. The adhesive is made of 100 parts of a main resin, 10-15 parts of a BMT type bismaleimide resin, 10-15 parts of a phenolic cyanate, 8-12 parts of a copolymer modifier, 15-30 parts of a rubber elastomer toughening agent, 4-12 parts of an inorganic nanofiller and 220-280 parts of a solvent by mass. The main resin is composed of an alkynyl-terminated isoimide resin. The copolymer modifier is composed of diallyl bisphenol A, allyl phenolic resin and vinyl-terminated nitrile rubber. BMT type bismaleimide resin, phenolic cyanate and diallyl bisphenol A, allyl phenolic resin, and vinyl-terminated nitrile rubber are prepared into a modified resin by copolymerization. However, the target of the high temperature resistant honeycomb node adhesive of Chinese patent CN104479620B is a polyimide paper honeycomb product. Since polyimide paper honeycombs and aluminum honeycombs have completely different properties, the high temperature resistant honeycomb node adhesive of Chinese patent CN104479620B cannot be used for node bonding of aluminum honeycomb structures. Summary of the invention

[0006] In view of the above problems, the present invention provides a heat-activated adhesive suitable for bonding nodes of aluminum honeycomb core stacking and a preparation method thereof. The heat-activated adhesive of the present invention is suitable for bonding between aluminum honeycomb core stacking layers. The adhesive layer after being coated on the surface of aluminum foil and dried is non-sticky at room temperature. When used, the multi-layer aluminum foil stacking is compacted by pressure, and the aluminum foil stacking is firmly bonded by heating activation. After the aluminum foil stacking is unfolded, a precise honeycomb design structure is formed and the nodes are not broken.

[0007] In a first aspect, the present invention provides a heat-activated adhesive suitable for bonding aluminum honeycomb core laminated nodes. The raw material composition of the heat-activated adhesive suitable for bonding aluminum honeycomb core laminated nodes includes: by mass percentage, 30-55% acrylonitrile-butadiene copolymer, 30-45% bisphenol A epoxy resin, 0.5-5% rubber vulcanizer, 5-18% epoxy curing agent, and 0.5-5% coupling agent; the solvent is not included in the raw material composition of the heat-activated adhesive suitable for bonding aluminum honeycomb core laminated nodes.

[0008] Preferably, the raw material composition of the heat-activated adhesive suitable for bonding the laminated nodes of the aluminum honeycomb core includes: in mass percentage, 30-55% acrylonitrile-butadiene copolymer, 30-45% bisphenol A epoxy resin, 0.5-5% rubber vulcanizer, 5-18% epoxy curing agent, 0.01-20% filler, and 0.5-5% coupling agent; the solvent is not included in the raw material composition of the heat-activated adhesive suitable for bonding the laminated nodes of the aluminum honeycomb core.

[0009] Preferably, the Mooney viscosity of the acrylonitrile-butadiene copolymer is 50 to 140, preferably 75 to 100. Mooney viscosity, also known as rotational (Mooney) viscosity, is a value measured by a Mooney viscometer and can reflect the degree of polymerization and molecular weight of the synthetic rubber.

[0010] Preferably, the bisphenol A epoxy resin is a solid (room temperature) bisphenol A epoxy resin with a softening point of 60-140°C; preferably, the bisphenol A epoxy resin is a solid (room temperature) bisphenol A epoxy resin with a softening point of 80-100°C.

[0011] Preferably, the mass ratio of the bisphenol A epoxy resin to the acrylonitrile-butadiene copolymer is 1:(0.5-2); preferably, the mass ratio of the bisphenol A epoxy resin to the acrylonitrile-butadiene copolymer is 1:(0.8-1.26).

[0012] Preferably, the acrylonitrile-butadiene copolymer is selected from one or more of unmodified ordinary acrylonitrile-butadiene copolymer, carboxyl-modified carboxyl-terminated acrylonitrile-butadiene copolymer, and epoxy-modified epoxy-terminated acrylonitrile-butadiene copolymer.

[0013] Preferably, the rubber vulcanizing agent is selected from one or more of sulfur, sulfur-containing accelerators, and peroxides; preferably, the peroxide is dicumyl peroxide.

[0014] Preferably, the epoxy curing agent is selected from one or more of dicyandiamide and its modified products, 4,4-diaminodiphenyl sulfone, and microspheres containing room temperature epoxy curing agent.

[0015] Preferably, the filler is selected from one or more of calcium carbonate, magnesium carbonate, silicon dioxide, aluminum oxide, zinc oxide, calcium oxide, magnesium oxide, silicon powder, titanium dioxide, calcium hydroxide, magnesium hydroxide, aluminum hydroxide, white carbon black, and carbon black.

[0016] Preferably, the coupling agent is a silane coupling agent; preferably, the silane coupling agent is selected from one or more of γ-glycidyloxypropyltrimethoxysilane, (3-glycidylpropoxy)trimethoxysilane, 3-aminopropyltriethoxysilane, and γ-methacryloxypropyltrimethoxysilane.

[0017] In a second aspect, the present invention provides a method for preparing a heat-activated adhesive suitable for bonding laminated nodes of aluminum honeycomb cores. The preparation method comprises: dissolving and / or finely distributing the raw material components of the heat-activated adhesive suitable for bonding laminated nodes of aluminum honeycomb cores in a solvent respectively, and then mixing them evenly to obtain the heat-activated adhesive suitable for bonding laminated nodes of aluminum honeycomb cores; or, the preparation method comprises: plasticizing acrylonitrile-butadiene copolymer and rubber vulcanizer or rubber vulcanizer and filler by internal mixing or open mixing to obtain a plasticized product, and then dissolving and / or finely distributing the plasticized product and the remaining raw material components of the heat-activated adhesive suitable for bonding laminated nodes of aluminum honeycomb cores in a solvent respectively, and then mixing them evenly to obtain the heat-activated adhesive suitable for bonding laminated nodes of aluminum honeycomb cores.

[0018] Preferably, the solvent is a good solvent of the raw material composition of the heat-activated adhesive suitable for bonding the aluminum honeycomb core laminated nodes; preferably, the solvent is selected from one or more of ethyl acetate, acetone, butanone and toluene.

[0019] Beneficial Effects

[0020] The heat-activated adhesive of the present invention is suitable for bonding between aluminum honeycomb core layers. The adhesive layer after being coated on the surface of aluminum foil and dried is non-sticky at room temperature, and can be repeatedly positioned regardless of whether the aluminum foil is stacked by machine or by hand. Moreover, the multi-layer aluminum foil stacking using the adhesive is compacted by pressure, and the aluminum foil stacking is firmly bonded by heating activation, and the aluminum foil stacking forms a precise honeycomb design structure after the aluminum foil stacking is unfolded, and the nodes are not broken. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a diagram showing the effect of glue lines for bonding the laminated nodes of the aluminum honeycomb core of Example 1.

[0022] Figure 2 Schematic diagram of aluminum foil coating and stretching for bonding the aluminum honeycomb core laminated nodes of Example 1. A is a schematic diagram of aluminum foil unwinding and gluing; B is a schematic diagram of aluminum foil staggered stacking after multiple layers of gluing, entering the hot press after stacking, and forming a firm bond after heat activation; C is a schematic diagram of aluminum foil stretching after stacking. Among them, red is node glue and blue is aluminum foil.

[0023] Figure 3 This is a diagram showing the effect of glue lines for bonding the aluminum honeycomb core laminate nodes of Example 6. DETAILED DESCRIPTION

[0024] The present invention is further described by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.

[0025] The heat-activated adhesive for bonding the nodes of aluminum honeycomb core laminates according to the present invention may also be called aluminum honeycomb reactive adhesive or aluminum honeycomb node adhesive. The heat-activated adhesive for bonding the nodes of aluminum honeycomb core laminates according to the present invention comprises: acrylonitrile-butadiene copolymer, bisphenol A epoxy resin, rubber vulcanizer, epoxy curing agent, and coupling agent.

[0026] In some embodiments, the raw material composition of the heat-activated adhesive suitable for bonding the nodes of the aluminum honeycomb core laminate includes: by mass percentage, 30-55% acrylonitrile-butadiene copolymer, 30-45% bisphenol A epoxy resin, 0.5-5% rubber vulcanizer, 5-18% epoxy curing agent, and 0.5-5% coupling agent; the solvent is not included in the raw material composition of the heat-activated adhesive suitable for bonding the nodes of the aluminum honeycomb core laminate. After the aluminum honeycomb reactive adhesive of the present invention is intermittently coated on the surface of the aluminum foil and dried, it is non-sticky at room temperature, and after the multi-layer aluminum foil laminate is compacted by pressure, it is heated and activated to make the aluminum foil laminates firmly bonded to each other, and when the aluminum foil laminate is unfolded, a precise honeycomb design structure (such as a regular hexagonal honeycomb structure) is formed without breaking the nodes.

[0027] Acrylonitrile-butadiene copolymer can also be called nitrile rubber. In some technical solutions, the acrylonitrile content of the acrylonitrile-butadiene copolymer is 20-50wt%. For example, the acrylonitrile content of the acrylonitrile-butadiene copolymer is 25-49wt%. The acrylonitrile-butadiene copolymer with too low acrylonitrile content has poor solubility. In the embodiment, an acrylonitrile-butadiene copolymer with an acrylonitrile content of about 35-45wt% is specifically used.

[0028] The Mooney viscosity of the acrylonitrile-butadiene copolymer is 50 to 140. Preferably, the Mooney viscosity of the acrylonitrile-butadiene copolymer is 75 to 100. The Mooney viscosity is a physicochemical index well known in the art. The acrylonitrile-butadiene copolymer in the above-mentioned Mooney viscosity range belongs to a medium-high Mooney acrylonitrile-butadiene copolymer. The acrylonitrile-butadiene copolymer plays a role in ensuring the accuracy of the fixed glue coating line in the node glue system, and can also avoid the collapse of the glue line during the activation process with pressure and high temperature. After the acrylonitrile-butadiene copolymer with low Mooney viscosity is glued in the aluminum honeycomb product, the boundary is blurred, resulting in a decrease in the accuracy of the glue line. It is further manifested that after hot pressing, the glue line collapses due to the lack of high Mooney acrylonitrile-butadiene support, and after the aluminum foil is laminated, the actual bonding area is wider than the design value, resulting in the honeycomb structure not meeting the design shape, thereby failing to meet the use requirements. In the embodiment, an acrylonitrile-butadiene copolymer with a Mooney viscosity of 80 to 90 is specifically used.

[0029] The acrylonitrile-butadiene copolymer is selected from one or more of unmodified ordinary acrylonitrile-butadiene copolymer (ordinary nitrile rubber), carboxyl-modified acrylonitrile-butadiene copolymer (carboxyl-terminated butyl rubber), and epoxy-modified acrylonitrile-butadiene copolymer (epoxy-terminated butyl rubber). When multiple acrylonitrile-butadiene copolymers are used, the amount of each acrylonitrile-butadiene copolymer can be adjusted as needed.

[0030] In some embodiments, the bisphenol A epoxy resin is a solid bisphenol A epoxy resin with a softening point of 60 to 140°C. It was found during the experiment that only when the bisphenol A epoxy resin is solid at room temperature, the obtained node glue system is coated on the surface of the aluminum foil and dried, and the coating glue surface is not sticky. The inventor has also used a bisphenol A epoxy resin that is liquid at room temperature. However, when the bisphenol A epoxy resin is liquid at room temperature, the obtained node glue system is coated on the surface of the aluminum foil and dried. The coating glue surface becomes obviously sticky, which causes the aluminum foil to be misaligned during the lamination process. It is difficult to reposition it by sliding the upper aluminum foil. Since the node glue on the surface of the lower aluminum foil has already contacted the upper aluminum foil, if the upper aluminum foil is uncovered and placed for repositioning, it will cause at least part of the glue surface to be taken away by the upper aluminum foil during the uncovering process, causing the glue surface to peel off, fall off, and dislocate, etc., so that it cannot be used and produced normally. Moreover, when using bisphenol A epoxy resin that is liquid at room temperature, the aluminum honeycomb of the obtained node glue system presents a honeycomb structure that does not conform to the designed shape after being unfolded. This is because liquid bisphenol A has a lower viscosity during the hot pressing process and is easy to flow, causing the glue line to collapse and widen. After the aluminum foil laminate is unfolded, the actual bonding area is wider than the designed value, resulting in a honeycomb structure that does not conform to the designed shape, thereby failing to meet the use requirements. In the embodiment, a solid bisphenol A epoxy resin with a softening point of 85 to 90° C. is specifically used.

[0031] The bisphenol A epoxy resin of the present invention is not limited to a single bisphenol A epoxy resin. A combination of bisphenol A epoxy resins with multiple softening points can also be used. For example, a mixture of multiple bisphenol A epoxy resins with softening points of 60 to 140° C. is used.

[0032] The function of rubber vulcanizer is to promote the formation of cross-linked structure of rubber under heating conditions to increase strength. Rubber vulcanizer includes but is not limited to sulfur, sulfur-containing accelerators, peroxides (such as diisopropylbenzene peroxide), etc.

[0033] The epoxy curing agent is a latent curing agent that does not react at room temperature, but can release activity and react with epoxy groups at high temperatures. Epoxy curing agents include but are not limited to dicyandiamide and its modified products (such as dicyandiamide powder), 4,4-diaminodiphenyl sulfone, microspheres containing room temperature curing agents (epoxy curing agents are encapsulated in microspheres), etc.

[0034] The filler is an inert material and does not participate in the activation reaction. The filler includes but is not limited to calcium carbonate, magnesium carbonate, silicon dioxide, aluminum oxide, zinc oxide, calcium oxide, magnesium oxide, silicon micropowder, titanium dioxide, calcium hydroxide, magnesium hydroxide, aluminum hydroxide, white carbon black, carbon black, etc.

[0035] The coupling agent can promote the improvement of the interfacial bonding strength between the adhesive and the aluminum alloy. The coupling agent includes but is not limited to a silane coupling agent. Commonly used silane coupling agents can be used. Including but not limited to γ-glycidyloxypropyltrimethoxysilane, (3-glycidyloxy)trimethoxysilane, 3-aminopropyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, etc.

[0036] The raw material composition of the heat-activated adhesive suitable for bonding the aluminum honeycomb core laminate nodes may also include an initiator. The initiator includes but is not limited to a free radical initiator or an activator.

[0037] The invention also discloses a method for preparing the heat-activated adhesive suitable for bonding the laminated nodes of the aluminum honeycomb core.

[0038] The preparation method comprises: respectively dissolving and / or finely distributing the raw material components of the heat-activated adhesive suitable for bonding the aluminum honeycomb core laminated nodes in a solvent, and then mixing them evenly to obtain the heat-activated adhesive suitable for bonding the aluminum honeycomb core laminated nodes.

[0039] Alternatively, the preparation method comprises: plasticizing acrylonitrile-butadiene copolymer and rubber vulcanizer or rubber vulcanizer and filler by internal mixing or open mixing to obtain a plasticized product; then dissolving and / or finely distributing the plasticized product and the remaining raw material components of the heat-activated adhesive suitable for bonding the laminated nodes of the aluminum honeycomb core respectively in a solvent, and then mixing them evenly to obtain the heat-activated adhesive suitable for bonding the laminated nodes of the aluminum honeycomb core. That is, the filler can be directly distributed in the solvent without being plasticized, or can be first plasticized and then distributed in the solvent.

[0040] The solvent is preferably a good solvent for the above raw material composition, including but not limited to ethyl acetate, acetone, butanone, toluene, etc.

[0041] The heat-activated adhesive of the present invention is a phenolic-free heat-activated adhesive. The heat-activated adhesive of the present invention is suitable for bonding between aluminum honeycomb core laminates. The adhesive layer after being coated on the surface of the aluminum foil and dried is non-sticky at room temperature, and can be repeatedly positioned regardless of whether the aluminum foil is stacked by machine or manually. Moreover, the multi-layer aluminum foil laminate using the adhesive is compacted by pressure, and the aluminum foil laminates are firmly bonded by heating activation. After the aluminum foil laminate is unfolded, a precise honeycomb design structure is formed without broken nodes. Moreover, the heat-activated adhesive of the present invention does not use phenolic resin, has a high curing temperature, good heat resistance, can maintain bonding strength at high temperatures, is easy to laminate, and is environmentally friendly.

[0042] The following examples are further listed to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values ​​​​exemplified below.

[0043] Example 1

[0044] The raw materials (excluding solvent) of the heat-activated adhesive suitable for bonding the laminated nodes of the aluminum honeycomb core include: by mass percentage, (a) 45.7% of ordinary nitrile rubber, (b) 36.5% of solid bisphenol A epoxy resin (softening point is about 90°C), (c) 1.37% of sulfur, (d) 9.13% of 4,4-diaminodiphenyl sulfone, (e) 4.57% of magnesium carbonate, and (f) 2.73% of γ-glycidyl ether oxypropyl trimethoxy silane coupling agent. The mass ratio of the sum of the mass of the raw materials (excluding solvent) of the heat-activated adhesive suitable for bonding the laminated nodes of the aluminum honeycomb core to the mass of ethyl acetate is 1:8.

[0045] Ordinary nitrile rubber, sulfur, and ethyl acetate are weighed, fully stirred and dissolved in a stirrer to obtain a dispersion. Solid bisphenol A epoxy resin, 4,4-diaminodiphenyl sulfone, magnesium carbonate, and γ-glycidyloxypropyl trimethoxysilane coupling agent are added to the dispersion, and a high-speed disperser is used to fully dissolve and evenly disperse them to obtain the heat-activated adhesive suitable for bonding the laminated nodes of the aluminum honeycomb core.

[0046] Example 2

[0047] The raw materials (excluding solvent) of the heat-activated adhesive suitable for bonding the laminated nodes of the aluminum honeycomb core include: (a) 35.35% of ordinary nitrile rubber, (b) 5.05% of carboxyl-terminated butyl rubber, (c) 40.4% of solid bisphenol A epoxy resin (softening point is about 90°C), (d) 3.03% of diisopropylbenzene peroxide, (e) 8.08% of 4,4-diaminodiphenyl sulfone, (f) 4.04% of silicon micropowder, (g) 1.01% of titanium dioxide, and (h) 3.04% of γ-glycidyl ether oxypropyl trimethoxy silane coupling agent. The mass ratio of the sum of the mass of the raw materials (excluding solvent) of the heat-activated adhesive suitable for bonding the laminated nodes of the aluminum honeycomb core to the mass of ethyl acetate is 1:8.

[0048] Ordinary nitrile rubber, carboxyl-terminated butyl rubber, diisopropylbenzene peroxide, and ethyl acetate are weighed and fully stirred and dissolved in a stirrer to obtain a dispersion. Solid bisphenol A epoxy resin, 4,4-diaminodiphenyl sulfone, silicon micropowder, titanium dioxide, and γ-glycidyloxypropyl trimethoxysilane coupling agent are added to the above dispersion, and a high-speed disperser is used to fully dissolve and evenly disperse them to obtain the heat-activated adhesive suitable for bonding the laminated nodes of the aluminum honeycomb core.

[0049] Example 3

[0050] The raw materials (excluding solvent) of the heat-activated adhesive suitable for bonding the laminated nodes of the aluminum honeycomb core include: by mass percentage, (a) 38.28% of ordinary nitrile rubber, (b) 4.78% of terminal epoxy butyl rubber, (c) 38.28% of solid bisphenol A epoxy resin (softening point is about 90°C), (d) 2.87% of diisopropylbenzene peroxide, (e) 7.66% of dicyandiamide micropowder, (f) 4.78% of nano magnesium carbonate, and (g) 3.35% of γ-glycidyl ether oxypropyl trimethoxy silane coupling agent. The mass ratio of the sum of the mass of the raw materials (excluding solvent) of the heat-activated adhesive suitable for bonding the laminated nodes of the aluminum honeycomb core to the mass of ethyl acetate is 1:8.1.

[0051] Ordinary nitrile rubber, epoxy-terminated butyl rubber, dicumyl peroxide, and ethyl acetate are weighed and fully stirred and dissolved in a stirrer to obtain a dispersion. Solid bisphenol A epoxy resin, dicyandiamide powder, nano magnesium carbonate, and γ-glycidyl ether oxypropyl trimethoxy silane coupling agent are added to the dispersion, and a high-speed disperser is used to fully dissolve and evenly disperse them to obtain the heat-activated adhesive suitable for bonding the laminated nodes of the aluminum honeycomb core.

[0052] Example 4

[0053] The raw materials (excluding solvent) of the heat-activated adhesive suitable for bonding the laminated nodes of the aluminum honeycomb core include: by mass percentage, (a) 37.55% of ordinary nitrile rubber, (b) 4.69% of terminal epoxy butyl rubber, (c) 37.56% of solid bisphenol A epoxy resin (softening point is about 90°C), (d) 2.83% of diisopropyl peroxide, (e) 9.39% of 4,4-diaminodiphenyl sulfone, (f) 4.69% of aluminum oxide, and (g) 3.29% of 3-aminopropyl triethoxysilane coupling agent. The mass ratio of the sum of the mass of the raw materials (excluding solvent) of the heat-activated adhesive suitable for bonding the laminated nodes of the aluminum honeycomb core to the mass of ethyl acetate is 1:8.

[0054] Ordinary nitrile rubber, epoxy-terminated butyl rubber, dicumyl peroxide, and ethyl acetate are weighed and fully stirred and dissolved in a stirrer to obtain a dispersion. Solid bisphenol A epoxy resin, 4,4-diaminodiphenyl sulfone, aluminum oxide, and 3-aminopropyl triethoxysilane coupling agent are added to the above dispersion, and a high-speed disperser is used to fully dissolve and evenly disperse them to obtain the heat-activated adhesive suitable for bonding the aluminum honeycomb core laminated nodes.

[0055] Example 5

[0056] The raw materials (excluding solvent) of the heat-activated adhesive suitable for bonding the laminated nodes of the aluminum honeycomb core include: by mass percentage, (a) 38.83% of ordinary nitrile rubber, (b) 4.85% of terminal epoxy butyl rubber, (c) 38.83% of solid bisphenol A epoxy resin (softening point is about 90°C), (d) 1.45% of sulfur, (e) 7.77% of dicyandiamide micropowder, (f) 4.85% of nano zinc oxide, and (g) 3.42% of γ-methacryloxypropyltrimethoxysilane coupling agent. The mass ratio of the sum of the mass of the raw materials (excluding solvent) of the heat-activated adhesive suitable for bonding the laminated nodes of the aluminum honeycomb core to the mass of ethyl acetate is 1:8.3.

[0057] Ordinary nitrile rubber, epoxy-terminated butyl rubber, sulfur, and ethyl acetate are weighed, fully stirred and dissolved in a stirrer to obtain a dispersion. Solid bisphenol A epoxy resin, dicyandiamide powder, nano zinc oxide, and γ-methacryloxypropyl trimethoxysilane coupling agent are added to the dispersion, and a high-speed disperser is used to fully dissolve and evenly disperse them to obtain the heat-activated adhesive suitable for bonding the aluminum honeycomb core laminated nodes.

[0058] Example 6

[0059] The raw materials (excluding solvent) of the heat-activated adhesive suitable for bonding the laminated nodes of the aluminum honeycomb core include: by mass percentage, (a) 40.83% of ordinary nitrile rubber, (b) 7.7% of terminal epoxy butyl rubber, (c) 38.83% of solid bisphenol A epoxy resin (softening point is about 90°C), (d) 1.45% of sulfur, (e) 7.77% of dicyandiamide powder, and (f) 3.42% of γ-methacryloxypropyltrimethoxysilane coupling agent. The mass ratio of the sum of the mass of the raw materials (excluding solvent) of the heat-activated adhesive suitable for bonding the laminated nodes of the aluminum honeycomb core to the mass of ethyl acetate is 1:8.3.

[0060] Ordinary nitrile rubber, epoxy-terminated butyl rubber, sulfur, and ethyl acetate are weighed, fully stirred and dissolved in a stirrer to obtain a dispersion. Solid bisphenol A epoxy resin, dicyandiamide powder, and γ-methacryloxypropyl trimethoxysilane coupling agent are added to the dispersion, fully dissolved and evenly dispersed using a high-speed disperser to obtain the heat-activated adhesive suitable for bonding the aluminum honeycomb core laminated nodes.

[0061] Comparative Example 1

[0062] The raw materials (excluding solvent) of the comparative aluminum honeycomb node glue include: by mass percentage, (a) 42.55% of common nitrile rubber, (b) 21.28% of thermosetting phenolic resin formed by base catalysis, 21.28% of solid bisphenol A epoxy resin (softening point is about 90°C), (c) 1.6% of sulfur, (d) 4.26% of dicyandiamide powder, (e) 5.32% of nano calcium carbonate, and (f) 3.71% of γ-glycidyl ether oxypropyl trimethoxy silane coupling agent. The mass ratio of the sum of the raw materials (excluding solvent) of the comparative aluminum honeycomb node glue to ethyl acetate is 1:9.

[0063] Ordinary nitrile rubber, sulfur, and ethyl acetate were weighed and fully stirred in a stirrer to dissolve and disperse to obtain a dispersion. Thermosetting phenolic resin, solid bisphenol A epoxy resin, dicyandiamide powder, nano calcium carbonate, and γ-glycidyloxypropyl trimethoxysilane coupling agent formed by base catalysis were added to the dispersion, and fully dissolved and dispersed uniformly using a high-speed disperser to obtain the comparative aluminum honeycomb node glue.

[0064] Comparative Example 2

[0065] The raw materials (excluding solvent) of the comparative aluminum honeycomb node glue include: by mass percentage, (a) 42.55% of common nitrile rubber, (b) 21.28% of thermosetting phenolic resin formed by acid catalysis, 21.28% of solid bisphenol A epoxy resin (softening point about 90°C), (c) 1.6% of sulfur, (d) 4.26% of dicyandiamide powder, (e) 5.32% of nano calcium carbonate, and (f) 3.71% of γ-glycidyl ether oxypropyl trimethoxy silane coupling agent. The mass ratio of the sum of the raw materials (excluding solvent) of the comparative aluminum honeycomb node glue to ethyl acetate is 1:9.

[0066] Ordinary nitrile rubber, sulfur, and ethyl acetate were weighed and fully stirred and dissolved in a stirrer to obtain a dispersion. A thermoplastic phenolic resin, solid bisphenol A epoxy resin, dicyandiamide powder, nano calcium carbonate, and γ-glycidyloxypropyl trimethoxysilane coupling agent formed by acid catalysis were added to the dispersion, and a high-speed disperser was used to fully dissolve and evenly disperse them to obtain the comparative aluminum honeycomb node glue.

[0067] Comparative Example 3

[0068] The raw materials (excluding solvent) of the comparative aluminum honeycomb node glue include: by mass percentage, (a) 42.55% of common nitrile rubber, (b) 17.02% of thermosetting phenolic resin formed by acid catalysis, (c) 21.28% of solid bisphenol A epoxy resin (softening point is about 90°C), (d) 4.25% of hexamethylenetetramine, (e) 1.6% of sulfur, (f) 4.26% of dicyandiamide powder, (g) 5.32% of nano calcium carbonate, and (h) 3.72% of γ-glycidyl ether oxypropyl trimethoxy silane coupling agent. The mass ratio of the sum of the raw materials (excluding solvent) of the comparative aluminum honeycomb node glue to ethyl acetate is 1:9.

[0069] Ordinary nitrile rubber, sulfur, and ethyl acetate were weighed and fully stirred in a stirrer to dissolve and disperse to obtain a dispersion. Thermoplastic phenolic resin, hexamethylenetetramine, solid bisphenol A epoxy resin, dicyandiamide powder, nano calcium carbonate, and γ-methacryloxypropyl trimethoxysilane coupling agent formed by acid catalysis were added to the dispersion, and a high-speed disperser was used to fully dissolve and evenly disperse them to obtain the comparative aluminum honeycomb node glue.

[0070] Comparative Example 4

[0071] The raw materials (excluding solvent) of the comparative aluminum honeycomb node glue include: (a) 42.55% of common nitrile rubber, (b) 42.55% of liquid bisphenol A epoxy resin (commercially available 128 type epoxy resin), (c) 1.6% of sulfur, (d) 4.26% of dicyandiamide powder, (e) 5.32% of nano calcium carbonate, and (f) 3.72% of γ-glycidyl ether oxypropyl trimethoxy silane coupling agent, in terms of mass percentage. The mass ratio of the sum of the raw materials (excluding solvent) of the comparative aluminum honeycomb node glue to ethyl acetate is 1:9.

[0072] Ordinary nitrile rubber, sulfur, and ethyl acetate were weighed and fully stirred and dissolved in a stirrer to obtain a dispersion. Liquid bisphenol A epoxy resin, dicyandiamide powder, nano calcium carbonate, and γ-methacryloxypropyl trimethoxysilane coupling agent were added to the dispersion, and fully dissolved and evenly dispersed using a high-speed disperser to obtain the comparative aluminum honeycomb node glue.

[0073] Comparative Example 5

[0074] The raw materials (excluding solvent) of the comparative aluminum honeycomb node glue include: (a) liquid nitrile rubber (basically no Mooney viscosity) 42.55%, (b) solid bisphenol A epoxy resin (softening point about 90°C) 42.55%, (c) sulfur 1.6%, (d) dicyandiamide powder 4.26%, (e) nano calcium carbonate 5.32%, (f) γ-glycidyl ether oxypropyl trimethoxy silane coupling agent 3.72%. The mass ratio of the sum of the raw materials (excluding solvent) of the comparative aluminum honeycomb node glue to ethyl acetate is 1:9.

[0075] Liquid nitrile rubber, sulfur and ethyl acetate were weighed and fully stirred in a stirrer to dissolve and disperse to obtain a dispersion. Solid bisphenol A epoxy resin, dicyandiamide powder, nano calcium carbonate and γ-glycidyloxypropyl trimethoxysilane coupling agent were added to the dispersion and fully dissolved and dispersed uniformly using a high-speed disperser to obtain the comparative aluminum honeycomb node glue.

[0076] Comparative Example 6

[0077] The raw materials (excluding solvent) of the comparative aluminum honeycomb node glue include: (a) 23.47% of common nitrile rubber, (b) 64.73% of solid bisphenol A epoxy resin (softening point is 80° C.), (c) 0.47% of sulfur, (d) 5.64% of dicyandiamide powder, (e) 4.69% of γ-glycidyloxypropyltrimethoxysilane coupling agent, and (f) 1% of carbon black, in terms of mass percentage. The mass ratio of the sum of the raw materials (excluding solvent) of the comparative aluminum honeycomb node glue to ethyl acetate is 1:9.

[0078] Ordinary nitrile rubber, sulfur, and ethyl acetate were weighed and fully stirred and dissolved in a stirrer to obtain a dispersion. Solid bisphenol A epoxy resin, dicyandiamide powder, and γ-methacryloxypropyl trimethoxysilane coupling agent were added to the dispersion, and fully dissolved and dispersed uniformly using a high-speed disperser to obtain the comparative aluminum honeycomb node glue.

[0079] Comparative Example 7

[0080] The raw materials (excluding solvent) of the comparative aluminum honeycomb node glue include: by mass percentage, (a) 42.55% of common nitrile rubber, (b) 21.28% of tert-octylphenol formaldehyde resin (commonly known as octylphenol formaldehyde), (c) 21.28% of solid bisphenol A epoxy resin, (d) 1.6% of sulfur, (e) 4.25% of dicyandiamide powder, (f) 5.32% of nano calcium carbonate, and (g) 3.72% of γ-glycidyl ether oxypropyl trimethoxy silane coupling agent. The mass ratio of the sum of the raw materials (excluding solvent) of the comparative aluminum honeycomb node glue to ethyl acetate is 1:9.

[0081] Ordinary nitrile rubber, sulfur, and ethyl acetate were weighed and fully stirred in a stirrer to dissolve and disperse to obtain a dispersion. 4-tert-octylphenol formaldehyde resin, solid bisphenol A epoxy resin, dicyandiamide powder, nano calcium carbonate, and γ-glycidyl ether oxypropyl trimethoxy silane coupling agent were added to the dispersion, and a high-speed disperser was used to fully dissolve and evenly disperse them to obtain the comparative aluminum honeycomb node glue.

[0082] Performance Testing

[0083] The node glue prepared in each embodiment and comparative example was coated on the surface of 0.05 mm thick aluminum foil, cut and stacked layer by layer, and then activated and bonded at 200° C. and 10 MPa pressure for 1 hour.

[0084] Glue line clarity: The glue line clarity is determined by the naked eye. The glue lines on the surface of the aluminum honeycomb core laminate present a pattern formed by multiple dumbbells, rings or parallelograms arranged closely. If the pattern outline is clear, the glue line clarity is judged to be qualified. If the pattern boundary collapses, atomizes, blurs, etc., the glue line clarity is judged to be unqualified.

[0085] Honeycomb shape: In this experiment, the honeycomb shape is designed as a regular hexagon.

[0086] Glue line width increment after hot pressing (glue line width value): Since the node glue coating needs to go through a high temperature and high pressure process, the glue line will soften at high temperature and withstand pressure, so the glue line after molding is slightly wider than the design value. The industry generally believes that the glue line width value is better when it is below 50um. If the glue line width value is too much, it means that the bonding edge of the hexagon increases, which is easy to cause the hexagonal structure to deform.

[0087] Bonding strength: After cooling, test according to GJB130.3-86 "Test method for strength of bonded aluminum honeycomb core nodes".

[0088] The specific test results are shown in Table 1.

[0089] Table 1

[0090]

[0091] Figure 1 This is a diagram showing the effect of the glue lines of Example 1. It can be seen that the glue lines on the surface of the aluminum honeycomb core laminate clearly present a pattern formed by a plurality of closely arranged parallelograms.

[0092] Figure 2 Schematic diagram of aluminum foil coating and stretching for bonding the aluminum honeycomb core laminated nodes of Example 1. A is a schematic diagram of aluminum foil unwinding and gluing; B is a schematic diagram of aluminum foil staggered stacking after multiple layers of gluing, entering the hot press after stacking, and forming a firm bond after heat activation; C is a schematic diagram of aluminum foil stretching after stacking. Among them, red is node glue and blue is aluminum foil.

[0093] Phenolic resins are divided into acid-catalyzed phenolic resins, base-catalyzed phenolic resins, modified phenolic resins, etc. from the catalytic system. Phenolic resins are divided into thermosetting phenolic resins and thermoplastic phenolic resins from the curing type. Comparative Examples 1 to 3 use thermosetting phenolic resins formed by base catalysis or thermoplastic phenolic resins formed by acid catalysis, and Comparative Example 7 uses modified tert-octylphenol formaldehyde resin, and the obtained comparative aluminum honeycomb node glue has no bonding strength. Among them, Comparative Example 3 introduces hexamethylenetetramine on the basis of Comparative Example 2 to cure the heat-curing phenolic resin, but still does not obtain the expected bonding effect. The present invention tried aluminum honeycomb node agents of various phenolic resin systems in the research and development stage, but none of them had good bonding performance.

[0094] Please note that the adhesive of Chinese patent CN103254862A uses bisphenol A epoxy resin and phenolic resin, and has bonding properties. The adhesives of comparative examples 1 to 3 of the present invention have both bisphenol A epoxy resin and phenolic resin, but have basically no bonding strength. This is because the adhesive of CN103254862A acts on aramid paper. Aramid paper is a fiber pressed product with a rough surface and many holes. CN103254862A uses resin to soften at high temperature to infiltrate, penetrate and wrap the fiber, creating a physical anchoring effect at the microscopic level, thereby forming a good bonding interface. The object of the present invention is aluminum foil, the surface of which is very smooth, and the bonding effect can only be achieved by chemical bonding of the adhesive.

[0095] Comparative Example 4 uses liquid epoxy resin. Although the comparative aluminum honeycomb node glue obtained has good bonding performance, the glue surface is sticky, and the aluminum honeycomb presents a non-regular hexagonal shape after being unfolded. This is because the liquid epoxy resin is easy to flow under pressure and high temperature, causing the glue line to exceed the design value. Therefore, the aluminum honeycomb has a non-regular hexagonal deformation after being unfolded.

[0096] Comparative Example 5 uses liquid nitrile rubber. Although the comparative aluminum honeycomb node glue obtained has good bonding performance, the glue surface is slightly sticky, and the aluminum honeycomb also presents a non-regular hexagonal shape after unfolding. This is because the liquid nitrile rubber cannot play a good skeleton role, so the glue flows under pressure and high temperature, exceeding the boundary set by the glue line, so the aluminum honeycomb presents a non-regular hexagonal deformation after unfolding.

[0097] In Comparative Example 6, the quality of bisphenol A epoxy resin is significantly higher than that of nitrile rubber, and the aluminum honeycomb presents a non-regular hexagonal shape after being unfolded. This is because: the thermal activation stage of the aluminum honeycomb core needs to be completed under pressure. High pressure allows sufficient contact between the aluminum foils for bonding to be achieved. During the heating process, it is generally necessary to rise to above 185°C. This temperature exceeds the softening point of the epoxy resin, and the epoxy resin becomes a fluid. A sufficient proportion of nitrile rubber with an appropriate Mooney viscosity can act as a skeleton to support the glue line from deformation and collapse. Otherwise, the bisphenol A epoxy resin is easily flattened, causing the glue line to exceed the set boundary and present a deformed non-regular hexagon. Although Chinese patents CN101602925A and CN103173176B use a phenolic-free epoxy adhesive system, the quality of bisphenol A epoxy resin is significantly higher than that of nitrile rubber, and both use liquid epoxy resin. This is because Chinese patents CN101602925A and CN103173176B are both adhesives that are liquid at room temperature and have fluidity and viscosity. The required bonded structures can be tightly fitted at room temperature, and it is not strict to apply pressure later. This type of product is an adhesive in the traditional sense. In the present invention, the upper and lower aluminum foils cannot be sticky initially to facilitate positioning and stacking. High pressure must be applied later to exclude the air between the laminated layers so that the adhesive surface is tightly fitted to the upper and lower aluminum foil surfaces. The heat-activated adhesive suitable for bonding the aluminum honeycomb core laminated nodes described in the present invention is a phenolic-free aluminum honeycomb node glue. The mass ratio of bisphenol A epoxy resin and acrylonitrile-butadiene copolymer in the aluminum honeycomb node glue of the present invention is 1: (0.5~2). It can be seen that the quality of the bisphenol A epoxy resin and nitrile rubber in the node glue system of the present invention is comparable, which significantly reduces the usage of bisphenol A epoxy resin, while still ensuring the bonding strength of the aluminum honeycomb node glue and the aluminum honeycomb can be unfolded to form a precisely designed shape.

[0098] Figure 3This is a glue line effect diagram of the aluminum honeycomb core laminate node bonding of comparative example 6. It can be seen that the glue line on the surface of the aluminum honeycomb core laminate is blurred, and the glue line pattern cannot be clearly presented. Moreover, the aluminum honeycomb node glue of comparative example 5 is used for aluminum honeycomb core laminate node bonding. It is found that the glue line on the surface of the aluminum honeycomb core laminate is blurred, and the glue line pattern cannot be clearly presented.

Claims

1. Application of a heat-activated adhesive in bonding of aluminum honeycomb core laminated nodes, characterized in that: The raw material composition of the heat-activated adhesive includes: by mass percentage, 30-55% acrylonitrile-butadiene copolymer, 30-45% bisphenol A epoxy resin, 0.5-5% rubber vulcanizer, 5-18% epoxy curing agent, and 0.5-5% coupling agent; the solvent is not included in the raw material composition of the heat-activated adhesive; The Mooney viscosity of the acrylonitrile-butadiene copolymer is 75-140, the bisphenol A epoxy resin is a solid bisphenol A epoxy resin with a softening point of 80-140° C., and the mass ratio of the bisphenol A epoxy resin to the acrylonitrile-butadiene copolymer is 1:(0.5-2).

2. The use according to claim 1, characterized in that: The raw material composition of the heat-activated adhesive includes: in percentage by mass, 30-55% of acrylonitrile-butadiene copolymer, 30-45% of bisphenol A epoxy resin, 0.5-5% of rubber vulcanizer, 5-18% of epoxy curing agent, 0.01-20% of filler, and 0.5-5% of coupling agent; the solvent is not included in the raw material composition of the heat-activated adhesive.

3. The use according to claim 1, characterized in that: The mass ratio of the bisphenol A epoxy resin to the acrylonitrile-butadiene copolymer is 1:(0.8-1.26).

4. The use according to claim 1 or 2, characterized in that: The acrylonitrile-butadiene copolymer is selected from one or more of unmodified common acrylonitrile-butadiene copolymer, carboxyl-modified carboxyl-terminated acrylonitrile-butadiene copolymer and epoxy-modified epoxy-terminated acrylonitrile-butadiene copolymer.

5. The use according to claim 1 or 2, characterized in that: The rubber vulcanizing agent is selected from one or more of sulfur-containing accelerators and peroxides.

6. The use according to claim 5, characterized in that: The sulfur-containing accelerator is sulfur.

7. The use according to claim 1 or 2, characterized in that: The epoxy curing agent is selected from one or more of dicyandiamide, 4,4-diaminodiphenyl sulfone, and microspheres containing room temperature epoxy curing agent.

8. The use according to claim 2, characterized in that: The filler is selected from one or more of calcium carbonate, magnesium carbonate, silicon dioxide, aluminum oxide, zinc oxide, calcium oxide, magnesium oxide, silicon micropowder, titanium dioxide, calcium hydroxide, magnesium hydroxide, aluminum hydroxide, white carbon black, and carbon black.

9. The use according to claim 1 or 2, characterized in that: The coupling agent is a silane coupling agent.

10. The use according to claim 1, characterized in that: The preparation method of the heat-activated adhesive comprises: respectively dissolving and / or finely distributing the raw material components of the heat-activated adhesive in a solvent, and then mixing them evenly to obtain the heat-activated adhesive; or, the preparation method comprises: plasticizing acrylonitrile-butadiene copolymer and a rubber vulcanizer by internal mixing and open mixing to obtain a plasticized product, and then respectively dissolving and / or finely distributing the plasticized product and the remaining raw material components of the heat-activated adhesive in a solvent, and then mixing them evenly to obtain the heat-activated adhesive.

11. The use according to claim 2, characterized in that: The preparation method of the heat-activated adhesive comprises: respectively dissolving and / or finely distributing the raw material components of the heat-activated adhesive in a solvent, and then mixing them evenly to obtain the heat-activated adhesive; or, the preparation method comprises: plasticizing acrylonitrile-butadiene copolymer, rubber vulcanizer and filler by internal mixing and open mixing to obtain a plasticized product, and then dissolving and / or finely distributing the plasticized product and the remaining raw material components of the heat-activated adhesive in a solvent, and then mixing them evenly to obtain the heat-activated adhesive.

12. The use according to claim 10 or 11, characterized in that: The solvent is a good solvent of the raw material composition of the heat-activated adhesive; the solvent is selected from one or more of ethyl acetate, acetone, butanone and toluene.

Citation Information

Patent Citations

  • Halogen-free ethoxyline resin antiflaming bonding adhesive and adhesive film thereof

    CN101602925A

  • Bi-component modified epoxy adhesive and preparation method thereof

    CN103173176B

  • Sandwich adhesive for high-strength aramid fibre paper honeycomb and preparation method thereby

    CN103254862A

  • A kind of high temperature resistant honeycomb node adhesive and preparation method thereof

    CN104479620B

  • Method for manufacturing welded aluminum honeycomb core and special adhesive

    CN107738493A